Comparison of surgical results between 'atticosinuplasty' and canal wall up mastoidectomy for early-stage cholesteatoma. (1st April 2022) - Jang, Jeong Hun; Choo, Oak-Sung; Kim, Hantai; Park, Hun Yi; Choung, Yun-Hoon
Abstract: Background: We devised a surgical technique called 'atticosinuplasty' (AS) for the treatment of early-stage cholesteatoma. Objective: This study analyzed the adequacy and applicability of AS compared to canal wall-up mastoidectomy (CWU) in patients treated for early-stage cholesteatoma. Materials and Methods: A total of 187 patients with either AS ( n = 89) or CWU ( n = 98) were compared in terms of postoperative hearing outcome, recurrence and re-operation rate, and radiologic outcome. Results: Hearing gain was significant in the AS group ( p < 0.001) but not in the CWU group. Air conduction change, air–bone gap (ABG) change, and ABG closure did not significantly differ between the two groups. The frequencies of cholesteatoma recurrence and revision ossiculoplasty were also similar. Of the 32 patients in the AS group with only attic/sinus involvement preoperatively, 20 (62.5%) showed no haziness and 6 (18.8%) had haziness extending to the mastoid postoperatively. Among the 67 patients in the CWU group who had haziness extending to the mastoid preoperatively, in 54 (80.6%) there was no change postoperatively. Conclusions and Significance: AS is a surgical technique worth trying in patients with early stage of attic/sinus cholesteatoma in terms of the rate of recurrence and hearing improvement.